The Growth of Transport Sector CO2 Emissions and Underlying Factors in Latin America and the Caribbean - Timilsina, Govinda R.; Shrestha, Ashish (World Bank, Washington, DC, 2012)
This study examines the factors responsible for the growth of transport sector carbon dioxide emissions in 20 Latin American and Caribbean countries during 1980-2005 by decomposing the emissions growth into components associated with changes in fuel mix, modal shift, and economic growth, as well as changes in emission coefficients and transportation energy intensity. The key finding of the study is that economic growth and the changes in transportation energy intensity are the main factors driving transport sector carbon dioxide emissions growth in the countries considered. The results imply that fiscal policy instruments - such as subsidies to clean fuels and clean vehicles - would be more effective in reducing emissions in countries where the economic activity effect is the primary driver for transport sector carbon dioxide emissions growth. By contrast, regulatory policy instruments - such as vehicle efficiency standards and vehicle occupancy standards - would be more effective in countries where the transportation energy intensity effect is the main driver of carbon dioxide emissions growth. Both fiscal and regulatory policy instruments would be useful in countries where both economic activity and transportation energy intensity effects are responsible for driving transport sector carbon dioxide emissions growth.